Wiener-Hosoya energy of non-commuting graph for dihedral groups - Romdhini, M.U.; Nawawi, A.; Al-Sharqi, F.; Al-Quran, A.; Kamali, S.R. (Asia Pacific Academic, 2024)
Spectral graph theory studies the connection between graph theory and algebra through matrices representation. This research is devoted to the spectrum of the non-commuting graph for the dihedral group. The matrix representation is the Wiener-Hosoya matrix which is a square matrix and the eigenvalues corresponding to the matrix are determined. The result shows that the energy is always similar to twice its spectral radius.